Liaison psychiatry - Cárdenas Salazar, Bolívar; Moncayo Cárdenas, Vicente (Revista Universidad de Guayaquil, 1990)
Liaison Psychiatry, an updated term as a modern and social-scientific conceptualization of Medicine; which indicates the intimate relationship that exists and must exist with the other areas of Medical Science, in which the Psychiatrist is linked and is fully accepted by the other areas. And with this, greater coverage by the Psychiatrist in a General Hospital, giving timely attention to Interconsultations; At the IESS Regional Hospital, the Ligature-Link was optimized around the year 1981, when the Psychiatric Hospitalization Unit was created, thus complementing the Psychiatry Service of this Hospital. That we objectify it, when analyzing the statistical table of Interconsultations attended; those coming from the other Hospitalization areas, those from other Outpatient Clinics and other Units of the Institute, in addition to other Provinces including Agricultural and Peasant Insurance, which I will explain later.